1997
DOI: 10.1099/0022-1317-78-7-1521
|View full text |Cite
|
Sign up to set email alerts
|

Differences in hepatitis C virus quasispecies composition between liver, peripheral blood mononuclear cells and plasma.

Abstract: Hepatitis C virus (HCV) exists in vivo as a highly variable mixture of closely related genomes (quasispecies), but the pathogenetic significance of such heterogeneity is still largely unknown. To investigate this issue, we compared the composition of HCV quasispecies found in the liver, peripheral blood mononuclear cells (PBMC) and plasma of ten patients by single-strand conformation polymorphism analysis of the E2/NS1 region and sequencing of the variants detected. We found considerable quasispecies differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 18 publications
7
66
1
Order By: Relevance
“…The quasispecies nature of HCV seemed to relate to the pathogenesis of persistent infection 8,9,22,23 and to the effectiveness of interferon therapy, 5,10,11 but its pathogenetic significance is still unknown. Although, hepatocytes are thought to be the principal site of HCV replication, there have only been a few studies on the quasispecies nature of liver [12][13][14]24 and the results of these studies were conflicting. Sakamoto et al reported no difference in diversity of HCV quasispecies between plasma and liver from data obtained by single-strand conformation polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…The quasispecies nature of HCV seemed to relate to the pathogenesis of persistent infection 8,9,22,23 and to the effectiveness of interferon therapy, 5,10,11 but its pathogenetic significance is still unknown. Although, hepatocytes are thought to be the principal site of HCV replication, there have only been a few studies on the quasispecies nature of liver [12][13][14]24 and the results of these studies were conflicting. Sakamoto et al reported no difference in diversity of HCV quasispecies between plasma and liver from data obtained by single-strand conformation polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…[79][80][81] While some of these data should be viewed cautiously, as a variety of techniques were utilized and a limited number of samples [82][83][84] Interestingly, sequence analysis has subsequently revealed that certain viral variants may be selected for growth in extrahepatic cell types, implying that HCV diversity directly impacts cell tropism. 85,86 Furthermore, several studies have described a non-random distribution of HCV sequences in hepatic and extrahepatic compartments, 72,[87][88][89][90][91][92][93][94][95][96] leading to the conclusion that the presence of tissue-specific sequences is compatible with independent viral replication in extrahepatic sites. It has also been speculated that HCV variants within distinct compartments may differ in their sensitivity to interferon, although this hypothesis has not been formally tested.…”
Section: Evidence For Extrahepatic Replication Of Hcvmentioning
confidence: 99%
“…Comparison of PCR products amplified from such divergent and rapidly changing regions is technically challenging ; for example, as the template copy number in these studies was not adjusted and a relatively small number of clones was studied, part of the observed quasispecies heterogeneity could be artificial and represent sampling variations compounded by Taq polymerase and cloning errors. The results of two other studies, in which HCV quasispecies were compared by singlestrand conformation polymorphism (SSCP) analysis, contradict each other (Maggi et al, 1997 ;Sakamoto et al, 1995). Again, both studies were conducted on the E2 hypervariable region and the template copy number was not adjusted for individual reactions.…”
Section: Introductionmentioning
confidence: 51%
“…When compared with previous reports (Cabot et al, 1997 ;Maggi et al, 1997 ;Navas et al, 1998 ;Sakamoto et al, 1995 ;Shimizu et al, 1997), the present study has several unique features. Firstly, it was conducted on the most conserved part of the viral genome, which lowers the chance of artefactual polymorphism being detected.…”
Section: Liver Serummentioning
confidence: 56%
See 1 more Smart Citation